Pra-Rancangan Pabrik Bioavtur dari Kelapa Sawit dengan Proses Hefa Kapasitas 100.000 Ton/Tahun - Intan Rahmatika El Putri Utami; Muhammad Agil Asshofy (Fakultas Teknik, 2025)
Aviation biofuel is an alternative jet fuel for turbine-engine aircraft, produced through a series of biomass conversion processes involving fiber, sugar, starch, and vegetable oils. The application of aviation biofuel as a blending component in jet fuel in Indonesia continues to show positive development, as reflected in government regulation stipulated in the Ministry of Energy and Mineral Resources Regulation No. 12 of 2015. This regulation mandates the blending of biofuel into jet fuel, starting from 2% in 2016 and increasing to 5% by 2025. In addition, aviation biofuel production is being carried out by PT Pertamina through Pertamina Refinery Unit IV Cilacap. With the increasing proportion of aviation biofuel blended into jet fuel, there is a significant opportunity to meet domestic demand and reduce jet fuel importation. This thesis presents the design of a aviation biofuel production plant with a capacity of 100,000 tons per year, utilizing palm oil biomass as the primary raw material. The production process involves three main stages: (1) raw material preparation by extracting and refining palm oil into CPO using phosphoric acid and bleaching earth, (2) hydrotreating reaction, in which triglycerides and free fatty acids (FFA) react with hydrogen followed by hydrocracking to convert biodiesel components into aviation biofuel, and (3) product purification through gas-liquid separation and distillation to obtain aviation biofuel with a purity of 98.35%. The analysis shows that the plant can produce 12,626.26 kg of aviation biofuel per hour from 80,026.34 kg of palm oil. The economic evaluation indicates a net profit of Rp 219.788.444.712, a return on investment (ROI) of 39,44%, and a payback period (POT) of 2.02 years. The break even point (BEP) is achieved at 48.94%. Based on this economic assessment, the proposed aviation biofuel production plant with a capacity of 100,000 tons per year is feasible to establish and has the potential to support government regulations, reduce jet fuel imports, manage biomass waste, and create job opportunities.
Reupload File Repository 19 Mei 2026_Yudi
Keywords: Aviation Biofuel; Biomass; UOP; Renewable; Economic Analysis